Exploiting next generation sequencing techniques (NGS) to identify molecular markers for monitoring the resistance of Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) to insecticides and Bt proteins - Nascimento, Antonio Rogerio Bezerra do (2018)
In this study we used Next-generation sequencing \"NGS\" for DNA and RNA sequencing to search for molecular markers associated with resistance of Spodoptera frugiperda (J.E. Smith) to insecticides and Bacillus thuringiensis Berliner (Bt) proteins. For this purpose, we selected S. frugiperda resistant strains to insecticides (chlorpyrifos, lambda-cyhalothrin, lufenuron, teflubenzuron and spinosad) belonging to different chemical groups and to the YieldGard VT-PRO® maize expressing Cry1A.105 and Cry2Ab2 proteins. The results of gene expression between resistant and susceptible strains of the neurotoxic insecticides chlorpyrifos and lambda-cyhalothrin demonstrated 935 differentially expressed genes associated with chlorpyrifos resistance and 241 differentially expressed genes associated with lambda-cyhalothrin. Most of these genes was related to high levels of expression in detoxification enzymes, especially the CYP3 and CPY6 families. Regarding to the insecticide teflubenzuron, the inheritance of resistance was characterized as autosomal, incompletely recessive and polygenic. The results of gene expression between resistant and susceptible strains of teflubenzuron indicated 3,519 differentially expressed transcripts, mainly detoxification enzymes from the GSTs, UGTs, P450s, CEs, as well as transport and regulation genes. This gene expression profile was also identified to YieldGard VT-PRO® resistant strain, which also demonstrated changes in the expression levels of other gene groups such as cadherin, aminopeptidases and alkaline phosphatase. Finally, to identify SNP markers associated with resistance of S. frugiperda to insecticides and Bt proteins, we used a genotyping by sequencing (GBS) protocol to all resistant strains and the susceptible strain. A total of 4,276 SNPs was recovered after filtering processes, where 53 polymorphic loci under selection were statistically significant (FDR<=0.047) and none of them was associated with coding regions. However, several of these SNPs were associated with regulatory regions of the genome. Analyses using DAPC resulted in the formation of seven clusters, with the susceptible line being separated from all resistant strains. The resistant strain to chlorpyrifos presented an exclusive cluster separated from the other resistant strains, which were grouped together. The association analyses between susceptible and resistant strains indicated 17 loci associated with all resistant strains, 114 loci associated with resistance to chlorpyrifos, 105 to lambda-cyhalothrin, 84 to lufenuron, 87 to teflubenzuron, 108 to spinosad and 62 to YieldGard VT-PRO® maize. Therefore, we can conclude that the resistance processes associated to insecticides and Bt toxins are due to a large number of molecular modifications at specific sites associated with detoxification and regulation processes. The use of technologies that allow for a systematic and comprehensive analyses of these phenomena, such as new-generation sequencing, large-scale molecular marker search, and functional studies with several insecticide groups should be the new research base to advance the knowledge on adaptive processes driven by the evolution of insect resistance to insecticides and Bt proteins.